Evaluation of Concept2 comp sweep blades - Kleshnev, V. (BioRow, 2023)
The Concept 2 Comp sculling blades have previously been tested in RBN 2020/11, 2021/10-11 and 2022/06. Recently, we have made our first biomechanical evaluation of the sweep version of the Comps, which have shorter spoon length (43cm) and smaller area compared to the standard Smoothie sweep blades (54cm). Two sets of oars for a coxless four were instrumented and calibrated. The oars had the following inboard / total length: